Pengaruh Pembiayaan Mudarabah terhadap Pendapatan Anggota/Nasabah - Royyan Ramdhani Djayusman; Achmad Nasution (University of Darussalam Gontor, 2015)
Mudarabah is a high risk product in Sharia banking and Islamic financial institutions. However, in Baitu-t Tamwil At-Tamzis, Mudarabah becomes as a superior product. The Mudarabah financing reaches Rp 6.592.378.131,- with profit rate Rp 219.235.450,- in 2013. After researching directly at Baitu-t Tamwil At-Tamzis, its capital and its clients’ finacing increase each year. The researcher aims to know the mecanism of mudarabah financing in Baitu-t Tamwil At-Tamzis and to know the influence of mudarabah financing to its clients’ income. This research is a field research using quantitative approach. To analyze the mecanism of mudarabah in Baitu-t Tamwil At-Tamzis, the researcher used analyzing/controlling method and interview, in other words the researcher controls the situation and work procedurs in Baitut Tamwil At-Tamzis. Whereas, to analyze its influence to its clients’ income, the researcher used analyzing/controlling method, interview, and documentation, it means that the researcher controls the activities of clients and interviews them, then referrs to the existing documentation as the first basis in formulating the research. To analyze the data obtained from the controlling, interview, and documentation method, the researcher use deductive and inductive method, and for analyzing approach, he uses statistics (regression) by employing SPSS 19 to analyze the influence of mudarabah financing to clients’ income. The result of analyzing statistic data is Adjusted r 2 0,571. It means 57,1% income variation can be explained by the variation of all three indepedent variables, namely trading times, capital, and experience. Whereas, the rest (100% - 57,1%= 42,9%) was explained by other reasons beyond the research model. The result of f-count is 45,012 larger than ftable. Therefore, H 0 was rejected. In other words, the independent variables which consist of trading times, capital, and experience simultaneously influence dependent variable (clients’ income). The capital has a significant value, t-count (4,090) > t-table (1,660) with significance 0,000 < (0,05), therefore H 0 was rejected and H 1 was accepted.